2013
DOI: 10.1111/ecoj.12058
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Suppliers and Market Power in Experimental Supply Function Competition

Abstract: We use experiments to study market power with supply function competition, akin to the competition in electricity markets. Our treatments vary the distribution of demand levels as well as the amount and symmetry of the allocation of production capacity between different suppliers. We relate our results to a descriptive power index and to the predictions of two models: a supply function equilibrium (SFE) model and a multi-unit auction (MUA) model. Observed behaviour is consistent with the equilibria of the unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…This guarantees that problem (66) has a unique optimal solution that is nonnegative elementwise, which, in turn, implies the optimality of this solution for problem (15). Let x ∈ R N + be the unique optimal solution to problem (66), which is a convex program with linear constraints. It follows that there exist Lagrange multipliers λ ∈ R and µ ∈ R 2m + such that the following conditions are satisfied.…”
Section: Appendix C Proof Of Propositionmentioning
confidence: 97%
“…This guarantees that problem (66) has a unique optimal solution that is nonnegative elementwise, which, in turn, implies the optimality of this solution for problem (15). Let x ∈ R N + be the unique optimal solution to problem (66), which is a convex program with linear constraints. It follows that there exist Lagrange multipliers λ ∈ R and µ ∈ R 2m + such that the following conditions are satisfied.…”
Section: Appendix C Proof Of Propositionmentioning
confidence: 97%
“…Holmberg et al (2013) provide a foundation for the continuous approach as an approximation to the discrete supply bids in a spot market. In their experimental work, Brandts et al (2014) …nd that observed behavior is more consistent with a supply function model than with a discrete multi-unit auction model.…”
mentioning
confidence: 90%
“…Exceptions include the work of Bolle et al (2013), who focus on testing predictions of Supply Function Equilibrium concept, as well as Brandts et al (2014), whose paper compares testable predictions made by various models of how pivotal suppliers affect supply function bidding. In contrast, our experiment focuses on a framework in which market power is driven by a small number of firms, increasing marginal costs, and private information about costs.…”
Section: Related Literaturementioning
confidence: 99%
“…All sessions were computerised. 8 Instructions were read aloud, questions were answered in private, and-throughout the sessions-no communication was allowed between subjects. Instructions explained all details of the market rules, distributional assumptions on the random costs, the nature of signals, and the correlation among costs (the meaning of correlation was explained both with a definition and graphically).…”
Section: Experimental Designmentioning
confidence: 99%